Integrasi Literasi Hukum Digital dalam Pendidikan Pancasila dan Kewarganegaraan - Zuhdi Arman (Jurnal Jejak Hukum Indonesia (JHI), 2026)
The rapid advancement of digital technology has transformed patterns of social interaction, including the exercise of citizens' rights and obligations in the digital sphere. At the same time, the increasing prevalence of cyber-related legal violations, such as the dissemination of misinformation, hate speech, privacy infringements, cyberbullying, and the misuse of personal data, demonstrates that digital literacy alone is insufficient to foster responsible citizenship. This condition highlights the importance of integrating digital legal literacy into Pancasila and Civic Education (Pendidikan Pancasila dan Kewarganegaraan/PPKn) as a strategic effort to strengthen legal awareness, civic character, and responsible citizenship grounded in the values of Pancasila and the Indonesian Constitution. This study aims to analyze the urgency of integrating digital legal literacy into Pancasila and Civic Education and to formulate a model for strengthening civic competencies that is responsive to technological developments. The study employs a normative legal research method using statutory, conceptual, and comparative approaches through the analysis of legislation, scholarly literature, and policy documents related to civic education, digital literacy, and cyber law. The findings indicate that the integration of digital legal literacy into Pancasila and Civic Education should emphasize strengthening students' understanding of citizens' rights and obligations in the digital environment, digital ethics, personal data protection, cybersecurity, and legal responsibility for digital activities. The implementation of this integration can be achieved through curriculum development, innovative case-based learning strategies, the effective use of educational technology, and the enhancement of teachers' professional competencies. Accordingly, Pancasila and Civic Education serves not only to develop democratic and morally responsible citizens but also to cultivate digitally competent citizens who are legally aware, ethical, critical, and accountable in responding to the challenges of digital transformation.